Current and future use of radiological images in the management of gynecological malignancies - a survey of practice in the UK - Dilley,J; Pratt,P; Kyrgiou,M; Flott,K; Darzi,A; Mayer,E (Anticancer Research, 2018)
Background/Aim: Radiology provides increasingly accurate and complex information. Understanding the clinicians' interpretation of scans could improve surgical planning, decision-making; informed training and development of augmented imaging. This was a survey exploring the interpretation of imaging by clinicians and its use in operative preparation and prediction. Materials and Methods: The survey was open for two-months and circulated online to British Gynaecological Cancer society members. Results: Seventy-three (19%) members completed the survey. Respondents had a confidence level of 51% in their ability to interpret computed tomography (CT) and/or magnetic resonance imaging (MRI) images independently. Preoperative imaging was commonly used to plan operations, predict complications and complete resection. Images were reviewed for primary (96.3%)/interval (92.6%) ovarian debulking, but less so for vulvectomy (45%). Scan (79.6%) and multidisciplinary team meeting (MDT) (66.6%) reports were used more often than scan images (50%) for operative planning. Amount and pattern of disease on scan were the most important factors predicting operating time. Conclusion: Imaging influences the surgeon's planning, however respondents lack confidence. Training of clinicians in radiological interpretation needs to improve. Augmented image interfaces could facilitate this.